1969
DOI: 10.1121/1.1911396
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Volumes in Normal Speech: A Possible Reason for Intraoral Pressure Differences among Voiced and Voiceless Consonants

Abstract: Respiratory volumes during phonation of a series of voiced and voiceless fricatives and plosives placed within a carrier phrase were measured in 20 normal adult subjects. The purpose was to (1) determine whether consonant type influences respiratory volume and (2) determine whether intraoral pressure differences among voiced-voiceless consonants could be a reflection of volume differences during speech. The results indicate that voiceless consonants utilize substantially larger volumes of air than their voiced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1977
1977
1996
1996

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Several investigators have shown that for the production of oral consonants, normal speakers typically generate levels of intra oral (supraglottal) air pressures within the mean range of 3.0-6.0 cm H20 [Arkebauer et al, 1967;Warren and Wood. 1969;Brown et al, 1970].…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators have shown that for the production of oral consonants, normal speakers typically generate levels of intra oral (supraglottal) air pressures within the mean range of 3.0-6.0 cm H20 [Arkebauer et al, 1967;Warren and Wood. 1969;Brown et al, 1970].…”
Section: Introductionmentioning
confidence: 99%
“…Warren and Wood [ 1969] found substantially greater re spiratory volumes during word-initial voice less stops than voiced stops of English. This finding led them to raise the question '... as to whether it is correct to assume that glot tal resistance during voicing is the major reason for intraoral pressure differences among consonants'.…”
Section: Role O F the Respiratory System During Speech Articulations mentioning
confidence: 96%
“…It has been argued that the respiratory system exerts greater expiratory force for the production of voiceless stops than voiced stops [Warren and Wood, 1969] and for the production of aspirated stops than unaspirated stops [Chomsky and Halle, 1968;Ladefoged et al, 1976]. Warren and Wood [ 1969] found substantially greater re spiratory volumes during word-initial voice less stops than voiced stops of English.…”
Section: Role O F the Respiratory System During Speech Articulations mentioning
confidence: 99%
See 1 more Smart Citation
“…air escape [Warren and Wood, 1969], There is evidence that the opening for fricatives does vary in size both within and among speakers, although the variations are small [Claypoole et al 1974: Klechak et al. 1976].…”
mentioning
confidence: 99%